A novel high-performance two poles and two zeros digital compensation control strategy for electric vehicle lithium battery charging systems. (25th August 2022) - Lee, Yu-Lin; Lin, Chang-Hua; Lu, Shiue-Der; Liu, Hwa-Dong
Abstract: This study proposes a 1 kW power converter of the lithium battery charging system for electric vehicles. Its proposed architecture comprises an interleaved boost power factor corrector (PFC) converter and a full-bridge phase-shift (FBPS) converter with a new two poles and two zeros (TPTZ) digital compensation function. Unlike the traditional one pole and one zero compensation control, the proposed TPTZ compensation control considers both the output voltage and the output current feedback, effectively controlling the gain bandwidth fc and phase margin PM and improving system stability and performance. The interleaved boost PFC converter can adjust the power factor close to 1.0. On the other hand, the FBPS converter adopts an average switching model and the duty cycle loss factor to derive the small-signal model of the full-bridge phase-shift converter. The model can obtain the transfer function of the output voltage and current to the duty cycle. The corresponding digital compensation control loop was designed and applied to the converters using the derived transfer function. Further, the charge system's stability with MATLAB simulation was verified. Finally, the proposed architecture with the proposed TPTZ control method was compared with the traditional battery charger architecture, in which the PFC converter was connected with an FBPS converter in series. The study found that the proposed battery charging system performs better than the traditional system under the test conditions (25 %, 50 %, and 100 % load). In addition, the proposed TPTZ method has 95 % and 96 % efficiency when charging with constant voltage mode and constant current mode at 100 % load, respectively. Furthermore, this study proposes a battery charging system with a TPTZ digital compensation function that not only improves system performance but also reduces circuit size, suitable for charging lithium batteries in electric vehicles. Highlights: The proposed is an interleaved PFC converter with a TPTZ digital compensation. The FBPS converter adopts an average switching model to derive a small-signal model. The proposed TPTZ method has 96 %, efficiency when charging mode at 100 % load.